Vaccination in Mexico: imprecise coverages and deficiency in the follow-up of children with incomplete immunization - Mauricio Hernández-Ávila; Lina Sofía Palacio-Mejía; Juan Eugenio Hernández-Ávila; Sofía Charvel (Instituto Nacional de Salud Pública, 2020)
Objective. To analyze the validity of the official vaccination figures according to the available information and to identify opportunities for improvement. Materials and methods. We estimated vaccination coverage and dropout rates (for multi-dose vaccines) for one-year-old children, based on public information from the dynamic cubes of the Ministry of Health, for the years 2015 to 2017. Results. We observed variations in the vaccination monthly reports, which indicate low rates of vaccination, as well as high dropout rates when comparing first and third doses applied. For children 1 year of age, the national complete coverage was estimated at 48.9%. Conclusion. There is no reliable information to estimate the actual vaccination coverage. Government documents report a constant overestimation of vaccination coverage that creates a "false sense of security". This has become a barrier for the critical analysis of the Universal Vaccination Program.